Evaluating the effect of hydroxyapatite nanoparticles on morphology, thermal stability and dynamic mechanical properties of multicomponent blend systems based on polylactic acid/Starch/Polycaprolactone. (9th August 2018) - Yavarpanah, Shakiba; Seyfi, Javad; Davachi, Seyed Mohammad; Hejazi, Iman; Khonakdar, Hossein Ali
Abstract: A hybrid of hydroxyapatite (HA) nanoparticles and encapsulated triclosan (LATC) was utilized to improve the overall performance of Polylactic acid/Starch/Polycaprolactone ternary blends. The morphological evaluations demonstrated that the starch component becomes gelatinized during the melt mixing process in the absence of LATC particles. However, once encapsulated triclosan particles were also added to the formulation, the granular structure of starch phase was retained indicating no gelatinization during the preparation process. In the case of nanocomposite samples, only 1 wt% of HA nanoparticles was found to exhibit a uniform distribution throughout the whole system whereas the higher concentrations resulted in the aggregation of nanoparticles dividing the system into HA‐poor and HA‐rich areas. Thermogravimetric analysis (TGA) was utilized to prove that those HA‐rich areas were formed around the starch domains due to the strong chemical affinity. Moreover, TGA also showed that only 1 wt% of HA nanoparticles acts efficiently in delaying the initiation of thermal decomposition. Dynamic mechanical analysis results also confirmed that HA nanoparticles had a strong tendency to be absorbed onto the starch domains within the system. J. VINYL ADDIT. TECHNOL., 25:E83–E90, 2019. © 2018 Society of Plastics Engineers